2010
DOI: 10.1017/s0317167100051556
|View full text |Cite
|
Sign up to set email alerts
|

iPhone-Based Teleradiology for the Diagnosis of Acute Cervico-Dorsal Spine Trauma

Abstract: An instant image transfer system can be used to support rapid medical and imaging decision making in an emergency situations when doctors are away from the hospital [1][2][3] . There are several Web-based picture archiving and communication systems, which allows access to a patient's radiological images from outside the hospital 1 . However, they are felt to be not appropriate for use in time-critical emergency cases as mentioned in previous studies 4,5 . Handheld devices like smart-phones and personal digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Researchers investigating the accuracies of a smartphone client-server teleradiology system compared to a dedicated workstation for acute stroke diagnosis reported specificity of 100 %, sensitivity of 94-97 %, and accuracy rates of 98-99 % [15]. We did not restrict the selection of emergency cases by diagnosis or body region, e.g., stroke, spine trauma, or acute appendicitis as in these studies [8,[15][16][17] but included a range of common emergent pathologies encountered in our hospital, including large angiographic studies with post-processed images. Our results suggest that the iPad is a viewing platform that has high levels of reporting concordance compared to PACS, regardless of the body region scanned, imaging protocols, and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers investigating the accuracies of a smartphone client-server teleradiology system compared to a dedicated workstation for acute stroke diagnosis reported specificity of 100 %, sensitivity of 94-97 %, and accuracy rates of 98-99 % [15]. We did not restrict the selection of emergency cases by diagnosis or body region, e.g., stroke, spine trauma, or acute appendicitis as in these studies [8,[15][16][17] but included a range of common emergent pathologies encountered in our hospital, including large angiographic studies with post-processed images. Our results suggest that the iPad is a viewing platform that has high levels of reporting concordance compared to PACS, regardless of the body region scanned, imaging protocols, and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Initial experience with such communication ranged from the use of digital cameras to obtain and transmit pictures of radiographic studies of orthopedic injuries [13,14] to closed circuit television and recording devices in the on-site evaluation, to provision of trauma care from the distance in real time. The simplicity of using smartphone technology to transmit images and recordings of patient wounds and radiographic images has been shown to be efficacious in more than one study [15,16], although their ubiquitous use has not occurred due to Health Insurance Portability and Accountability Act (HIPAA) concerns and the security of patient data. Within the last decade, more advanced technologic programs were created and demonstrated to be highly functional.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Several previous reports have demonstrated that there is no difference in the diagnostic accuracy for CT readings between smartphones and typical PACS workstations in various diseases [7,18,[20][21][22]. However, to the best of our knowledge, this is the first study to demonstrate the diagnostic Bperformance^of remote CT reading for acute appendicitis using a smartphone, which has good concordance with the performance of the PACS workstation LCD monitor under bright ambient lighting in a Brealistic ED setting^and using Breal-time data transmission^with a 3G network.…”
Section: Discussionmentioning
confidence: 64%
“…The iPhone 5 provides a similar image viewing quality compared to the clinical LCD monitor [7,18,[20][21][22]. The iPhone 5 has sufficient pixel pitch to support the radiology images at their original size and sufficient brightness and contrast to meet the ACR guideline recommendations for medical monitors [24].…”
Section: Discussionmentioning
confidence: 99%